Imaging Recommendations for Diagnosis, Staging, and Management of Oral Cancer - Mahajan, Abhishek; Agarwal, Ujjwal; PG, Nandakumar; Vaish, Richa; Shukla, Shreya; Sahu, Arpita; Bhalla, Ashu Seith; Patil, Vasundhara; Ankathi, Suman Kumar; Laskar, Sarbani Ghosh; Patil, Vijay; Noronha, Vanita; Menon, Nandini; Prabhash, Kumar; Shah, Diva; Patil, Asawari; Ahuja, Ankita; Chaturvedi, Pankaj; Pai, Prathamesh S.; Dcruz, A K (Indian Journal of Medical and Paediatric Oncology, 2023)
Oral cavity cancers contribute to a majority of cancers in India. Clinical examination alone cannot determine the deeper extent of the disease; therefore, need for cross-sectional imaging including computed tomography and magnetic resonance imaging becomes indispensable for pre-treatment evaluation to decide optimal plan of management. Oral cavity squamous cell cancers (OSCC) can be treated with surgery alone, whereas deep muscle, neurovascular, osseous, or nodal involvement on imaging suggests advanced disease that requires a combination of surgery, radiation, and/or chemotherapy. Because of the complex anatomy of the oral cavity and its surrounding structures, imaging is crucial for locoregional staging and early detection of distant metastases. Imaging plays indispensable role not only in diagnosis but also in planning the management. An optimal guideline paper for developing countries like India is lacking that not only helps standardize the management but will also assist oncologists make reasonable decisions and reduce the unnecessary imaging. This imaging guideline paper will discuss the optimal imaging in diagnosis and management OSCC for Indian subcontinent.
Keywords: computed tomography; guidelines; magnetic resonance imaging; oral cancer; imaging